APAcS star promoting graduate employability traits / Puteh Mariam Ismail, Normahiran Yatim and Norhayati Alias - Ismail, Puteh Mariam; Yatim, Normahiran; Alias, Norhayati (UiTM Press, 2020)
The issue of graduates' employability has become a growing concern globally. With many graduates, but limited positions in the workforce, it is imminent for graduates to possess employability traits. Employers also expect the students to learn a multitude of skills and abilities, on top of knowledge of accounting, while studying in the university. To reduce this gap, a student development framework, the APAcS Star was established. APAcS Star aims to bridge the gap by arming students with essential interpersonal skills. Based on three core Skill Areas, namely Critical Thinking, Communications and Leadership skills. APAcS Star is executed by further breaking those Skill Area into Traits. These traits connote an element of a Skill that, by mastering a number of those smaller Traits, will lead to a mastery of the major Skill. In conclusion, this framework was able to assist the higher education provider to craft and develop a multitude of skills and abilities of its graduates, thus reducing the employability gap.